Modeling and Control of a Hybrid Multi DOF Motor for a Tilted Rotating System - Hyun-Jong Park; Sung-Chul Go (Energies, 2022)
This paper presents the design, modeling, and control of a hybrid multi-degree-of-freedom motor (HMDOF motor) that can be applied to unmanned aerial vehicles, such as drones. The HMDOF motor has a rotating motor and tilting motors separately and enables multi-DOF movement by driving each motor. In addition, owing to its structural characteristics, it is designed to allow a 3- or 6-DOF movement in only one motor. In this study, the control performance of an HMDOF motor was verified using simulated and experimental results. The position control performance for the rotation speed of the rotating motor was verified, and the control performance of the motor under the speed of the rotating motor and disturbance on tilting motors were analyzed.